Serum Vascular Endothelial Growth Factor and Vascular Endothelial Growth Factor Receptor-1 Levels in Patients With Fibromyalgia Syndrome - Ahmet KARADAĞ; Emrullah HAYTA; Veysel Kenan ÇELİK and Sevtap BAKIR (Archives of Rheumatology, 2019)
Objectives: This study aims to compare the serum vascular endothelial growth factor (VEGF) and vascular endothelial growth factor receptor-1 (VEGFR-1) levels between patients with fibromyalgia syndrome (FMS) and healthy controls. Patients and methods: The study included 40 female patients (mean age 39.9±10.2 years; range, 22 to 52 years) diagnosed with primary FMS according to the American College of Rheumatology criteria (1990) and 40 healthy female volunteers (mean age 40.9±8.3 years; range, 25 to 53 years). The sociodemographic data of both groups were recorded. The disease duration and the number of tender points were recorded for patients with FMS, and venous blood samples were collected from the two groups for the measurement of serum VEGF and VEGFR-1 levels. Results: The FMS and control groups were comparable in terms of age and body mass index (p>0.05). A comparison of the serum VEGF levels of the FMS and control groups revealed a statistically insignificant difference (p>0.05), while a comparison of the serum VEGF-1 levels of the FMS and control groups revealed a statistically significant difference (p<0.05). Conclusion: Serum VEGFR-1 levels were higher in patients with FMS, while the serum VEGF levels of the FMS patients did not differ from those of the healthy controls.